Social Media And University Students During COVID-19 From The Point Of View Of Students College Of Food Sciences / Al-Qasim Green University (Texas Journal of Engineering and Technology, 2022)
The study's objective is to determine how new mental cognition affects people. When compared to the rising popularity of social media sites among professors and students, particularly during the COVID-19 sites, applications to these sites and the possibility of employment in them during the educational process, as well as recognizing the benefits of the pros and cons, these sites have a significant impact on the field of education. The descriptive method was used in the study. The research included a sample of (294) students from the College of Food Sciences / Al-Qasim Green University. To get data from samples, a questionnaire was employed. The most significant findings were that sites for social media had a significant role in the COVID-19 pandemic by connecting learners and educators and that using sites for social media for university education has many advantages. Create a strong infrastructure that facilitates the best possible use of these places, and offer some recommendations that will improve the likelihood of employment.